Candida species and other yeasts in the oral cavities of type 2 diabetic patients in Cali, Colombia (Colombia Medica, 2013)
Objective: To determine the prevalence of Candida species and to study factors associated to oral cavity colonization in patients with type 2 diabetes mellitus.Methods: A total of 107 diabetics were classified into controlled and uncontrolled according to glycosylated hemoglobin values. Each patient was assessed for stimulated salivary flow rates, pH, and an oral rinse to search for yeast. The study also determined the state of oral health via Klein and Palmer CPO indexes for permanent dentition, dental plaque by O’Leary, and a periodontal chart.Results: We found yeasts in 74.8% of the patients. A total of 36 of the 52 subjects with controlled diabetes presented yeasts and 44 in the uncontrolled; no significant differences (p= 0.2) were noted among the presence of yeasts and the control of blood glucose. The largest number of isolates corresponded to C. albicans, followed by C. parapsilosis. Uncontrolled individuals presented a significantly higher percentage of yeast different from C.albicans (p= 0.049).Conclusions: We found a high percentage of Candida colonization and uncontrolled individuals had greater diversity of species. The wide range of CFU/mL found both in patients with oral candidiasis, as well as in those without it did not permit distinguishing between colonization and disease. We only found association between isolation of yeasts and the low rate of salivary flow.